Case report: Severe hepatopathy following rivaroxaban administration in a dog - Mosichuk, Allison P.; Wimbish, Candace; Poplawski, Kristen; Birkenheuer, Adam; Harrell, Karyn; Pierce, Kursten V. (Frontiers in Veterinary Science, 2024)
Rivaroxaban, a specific factor Xa inhibitor and commonly utilized anticoagulant, has been known to cause hepatotoxicity and liver failure in humans. Although rivaroxaban is frequently used in veterinary medicine, hepatotoxicity has not been previously reported in dogs. The current case report describes a dog that developed a severe hepatopathy following rivaroxaban administration for a large right pulmonary artery thrombus. An estimated six-year-old spayed female mixed breed dog developed anorexia and lethargy nine days after rivaroxaban administration began. Subsequent labwork revealed a severe hepatocellular hepatopathy and rivaroxaban was discontinued. Additional diagnostics did not reveal an underlying etiology, although hepatic cytology could be consistent with a toxic injury. The hepatopathy and clinical signs improved after rivaroxaban was discontinued. The time to onset, type of hepatopathy, and time to resolution were all similar to those reported for human cases. This case provides precedence to advocate for improved and closer monitoring of dogs receiving factor Xa inhibitors. In cases of suspected hepatotoxicity with no other identifiable cause, a risk-benefit analysis should be performed, and discontinuation of rivaroxaban administration or alternative anticoagulant medications should be considered.